2016
DOI: 10.1177/2042098616642231
|View full text |Cite
|
Sign up to set email alerts
|

Medication safety in neonatal care: a review of medication errors among neonates

Abstract: Objective: The objective of this study was to describe the medication errors in hospitalized patients, comparing those in neonates with medication errors across the age spectrum. Method: In tier 1, PubMed, Embase and Google Scholar were searched, using selected MeSH terms relating to hospitalized paediatric, adult and elderly populations. Tier 2 involved a search of the same electronic databases for literature relating to hospitalized neonatal patients. Results: A total of 58 articles were reviewed. Medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 65 publications
(511 reference statements)
4
63
1
6
Order By: Relevance
“…6,7 There is also the associated challenge of limited dosing protocols and evidence-based information regarding the efficacy, safety, dosing, pharmacokinetic, and clinical use of medications in neonates. 6 In addition, relative physiological immaturity means that neonates have less capacity in being able to buffer unintended consequences of medication errors. 8 Such susceptibility towards medication errors in neonates, as previously described, is further emphasized by previous research that observed that medication errors with the potential to cause significant harm were three times more likely to occur in the neonatal intensive care unit (NICU) than in adult wards.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There is also the associated challenge of limited dosing protocols and evidence-based information regarding the efficacy, safety, dosing, pharmacokinetic, and clinical use of medications in neonates. 6 In addition, relative physiological immaturity means that neonates have less capacity in being able to buffer unintended consequences of medication errors. 8 Such susceptibility towards medication errors in neonates, as previously described, is further emphasized by previous research that observed that medication errors with the potential to cause significant harm were three times more likely to occur in the neonatal intensive care unit (NICU) than in adult wards.…”
Section: Introductionmentioning
confidence: 99%
“…MAEs are commonplace in healthcare settings, particularly in pediatric units (Gill et al, ). Murphy and While () found that the pediatric population experiences higher risk of MAEs (three times greater) than the adult population, as pediatric medication administration needs individualized dosing, very often using off‐label medication, and need to complex procedure of calculations to dosage, resulting in common MAEs (Krzyzaniak, & Bajorek, ). Hence, pediatric patients are considered to be an at‐risk group in terms of medication administration (Özkan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the clinical pharmacist has an important role to play in the quality use of medicines in this patient group, potentially having a large impact on patient outcomes 5. The high incidence of off-label medicines use, polypharmacy and frailty in this patient group (characterised by young gestational ages, very small birthweights) increases the risk of medication errors and poses challenges to the safe and effective use of pharmacotherapy 6. Studies have shown that pharmacist-led interventions can improve medication management in the NICU: daily bedside reviews of medication orders, individualised total parenteral nutrition (TPN) regimens and education programmes, have been shown to reduce medication errors 7 8…”
Section: Introductionmentioning
confidence: 99%